CHALLENGES AND OPPORTUNITIES OF MARKETING IN THE RESTAURANT INDUSTRY - Magalhães, Andrea Valim (Revista Sistemática, 2022)
The restaurant industry operates in a highly competitive and dynamic environment, where effective marketing plays a crucial role in organizational survival and growth. This article examines the main challenges and opportunities associated with restaurant marketing, drawing on established academic literature and professional experience. Key challenges include intensified market competition, rapid digital transformation, changing consumer expectations, and limitations in resources and marketing expertise. At the same time, opportunities emerge through digital marketing, social media engagement, relationship marketing, personalization strategies, and adaptive communication practices. By integrating theoretical insights with practical observations, this study highlights how strategic marketing approaches can help restaurants overcome structural constraints, strengthen customer relationships, and achieve sustainable competitive advantage in an increasingly complex marketplace.